2015
DOI: 10.1002/mnfr.201400780
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting effects of fresh and fermented kimchi consumption on gut microbiota composition and gene expression related to metabolic syndrome in obese Korean women

Abstract: Accumulating evidence suggests relationship of compositional changes of gut microbiota with onset of metabolic disorders and obesity. Kimchi, a traditional Korean side dish, is known for its beneficial impact on metabolic parameters and anti-obesity effects. The current study was designed to evaluate the association between gut microbiota and human genome after kimchi intervention in an effort to understand the molecular mechanism(s) underlying the antiobesity impact of kimchi. Twenty-four obese women were ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
104
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(109 citation statements)
references
References 17 publications
2
104
2
1
Order By: Relevance
“…) . Other studies have linked fermented foods such as Japanese fermented milk products and Korean kimchi to specific alterations in the microbiota including increased abundance of such Bifidobacteria …”
Section: The Asia‐pacific Region and The Microbiomementioning
confidence: 99%
See 1 more Smart Citation
“…) . Other studies have linked fermented foods such as Japanese fermented milk products and Korean kimchi to specific alterations in the microbiota including increased abundance of such Bifidobacteria …”
Section: The Asia‐pacific Region and The Microbiomementioning
confidence: 99%
“…51 Other studies have linked fermented foods such as Japanese fermented milk products and Korean kimchi to specific alterations in the microbiota including increased abundance of such Bifidobacteria. 56,57 Commensal Bifidobacteria can induce altered immune responses and are abundant in early life among Western populations but decline with age. 58,59 As the sustained prevalence of this bacterial group represents the most discernible difference between Asia-Pacific and Western microbiomes, it is interesting to speculate about its potential contribution to geographic variability in the rates of inflammatory diseases including those of the respiratory system.…”
Section: Respiratory Disease and The Microbiomementioning
confidence: 99%
“…The resulting fermented food, which is known to be healthy and beneficial, has been shown to possess enhanced nutritional value and health benefits because of the production of unique organic compounds and secondary metabolites by microbiological action 4 . For example, fermented food has been demonstrated to exhibit anti-obesity effects through altering gut microbiota composition and the expression of genes related to metabolic syndrome 5 . Among these fermented foods, vinegar, an acidic food seasoning, has recently received substantial attention because it was shown to exhibit multiple bioactivities, including anti-hypercholesterolaemia, anti-hyperglycaemia, anti-hypertension, anti-microbial, anti-thrombotic and even anti-cancer effects 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Of these, diet is considered a key contributor to the diversity of the gut microbiota, explaining 57% of the total structural variation, while only 12% is related to genetic differences [10]. Therefore, many studies have focused on the relationship between the gut microbiota and dietary factors, such as dietary pattern (vegetarian and Western) [11,12], specific foods (whole grain products, fruits, and vegetables) [13][14][15][16][17], and food constituents (dietary fiber, fat, and protein) [8,[18][19][20]. Interestingly, a recent study showed that European children who consumed a typical Western diet had a microbiota enriched in Firmicutes and Enterobacteriaceae, whereas rural African children, who consumed a diet low in fat and animal protein and rich in plant-based foods, had greater abundances of the genera Bacteroidetes and Prevotella [7].…”
Section: Introductionmentioning
confidence: 99%